Determination of anti-mullerian hormone in serum and ovarian histopathology of buffaloes - KEKAN, P M; INGOLE, S D; NAVEKAR, A S; BHARUCHA, S V; KHARDE, S D (The Indian Journal of Animal Sciences, 2020)
Present study was undertaken to assess AMH concentration in serum and histopathological study of AFC in buffalo ovaries. Total 30 pair of ovary were collected in 10% Neutral Buffer Formalin. Blood samples were also collected before slaughtering the buffalo animals for estimation of AMH concentration. Before processing, 10 serial sections of each pair of ovary was done for histopathological examinations. All the serial sections of the ovaries were processed as per the standard procedure. On the basis of histopathological examinations and follicle count, animals were categorized as cyclic and anestrus. Out of 30 pairs of ovary, 18 pairs were identified as anestrus and 12 as cyclic. The mean number of primordial, antral and growing ovarian follicles count of cyclic buffaloes were 0.42±0.07, 0.15±0.03 and 4.47±0.03 and 0.49±0.02, 0.16±0.03 and 0.41±0.06 for anestrus buffaloes, respectively. Growing follicles were significantly higher in cyclic as compared to anestrous buffaloes. However, the difference of primordial and antral follicle count remained non-significant in cyclic and anestrous buffaloes. Whereas, AMH concentration in cyclic buffaloes (273.50±48.52) was significantly higher than anestrous buffaloes (79.40±7.80). Therefore, it is concluded that, anti-mullerian hormone is an endocrine marker and can predict the fertility of animal. Also, follicular count is positively correlated with AMH concentration.